HUBUNGAN KARAKTERISTIK INOVASI DENGAN TINGKAT ADOPSI PETANI TERHADAP KOMPONEN PENGENDALIAN HAMA TERPADU (PHT) PADI SAWAH DI KELURAHAN LIABUKU KECAMATAN BUNGI KOTA BAUBAU - Wa Ode Dian Purnamasari (Media Agribisnis, 2019)
This research was conducted from November to December 2018 in Liabuku Village, Bungi Subdistrict, Baubau Town, with the aim of knowing the characteristics of innovation consisting of relative advantages, compatibility, complexity, trialability, and observability and types of innovation decisions in SLPHT rice plants; know the level of adoption of SLPHT farmers for integrated pest control components; know the relationship between the characteristics of innovation consisting of relative advantages, compatibility, complexity, trialability and observability, as well as the type of innovation decisions with the level of SLPHT farmers' adoption of the Integrated Pest Management (IPM) component. The number of respondents was 30 who had attended SLPHT. The data analysis technique used is the analysis of the average and standard deviations and Spearman rank correlation test. To find out the difference in the level of adoption of the IPM components of rice between SLPHT and Non-SLPHT farmers using the t-test. Based on the results of research and discussion, it is found that the characteristics of innovation of farmers provide a relative advantage for farmers, 60% of farmers say there is compatibility of trialability with pest control needs, and 40% of respondents state that innovation is sometimes not according to needs. The adoption rate of SLPHT farmers to the IPM component was 40% of farmers using varieties of lowland rice according to recommendations, 60% using superior rice not in accordance with recommendations. For fertilization, 20% of farmers fertilize according to recommendations, and 80% of farmers fertilize not according to recommendations. For integrated pest control, 50% of farmers conduct IPM, the remaining 50% carry out pest control with certain techniques. For the use of natural enemies, 83.33% of farmers did not utilize natural enemies, the rest, 16.67% did not use natural enemies. For routine observations, 90% of farmers do routine observations but not every week, only 10% of farmers do every week. And observations made are only part of the observation stages. For the wise use of pesticides, all farmers combine pesticides with other techniques. There is a significant relationship between the characteristics of compatibility innovation with the use of natural enemies as indicated by the sig correlation value is 0.05 smaller. There is a significant relationship between complexity with routine observations which is shown by the correlation sig value is 0.013 smaller 0.05. Keywords: Relationship, characteristics, innovation, adoption, IPM, farmers, lowland rice